2008
DOI: 10.1073/pnas.0712027105
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of the proteorhodopsin-containing marine bacterium Polaribacter sp. MED152 (Flavobacteria)

Abstract: Analysis of marine cyanobacteria and proteobacteria genomes has provided a profound understanding of the life strategies of these organisms and their ecotype differentiation and metabolisms. However, a comparable analysis of the Bacteroidetes, the third major bacterioplankton group, is still lacking. In the present paper, we report on the genome of Polaribacter sp. strain MED152. On the one hand, MED152 contains a substantial number of genes for attachment to surfaces or particles, gliding motility, and polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
253
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(278 citation statements)
references
References 39 publications
(51 reference statements)
11
253
0
1
Order By: Relevance
“…Since then, PRs have turned out to be highly abundant in the oceans (6)(7)(8)(9), and organisms containing them, including a cyanobacterium (10) can be found in many other habitats as well (7,(11)(12)(13). In vivo experiments have shown that pumping of protons by PR can lead to increases in growth rate under nutrient-limited conditions (6,14,15), production of ATP (16), increased fixation of CO 2 (6,17), and/or survival under starvation or stress conditions (16,(18)(19)(20). However, these enhancements generally require nutrient-limitation or stress conditions before they exceed experimental error.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, PRs have turned out to be highly abundant in the oceans (6)(7)(8)(9), and organisms containing them, including a cyanobacterium (10) can be found in many other habitats as well (7,(11)(12)(13). In vivo experiments have shown that pumping of protons by PR can lead to increases in growth rate under nutrient-limited conditions (6,14,15), production of ATP (16), increased fixation of CO 2 (6,17), and/or survival under starvation or stress conditions (16,(18)(19)(20). However, these enhancements generally require nutrient-limitation or stress conditions before they exceed experimental error.…”
Section: Introductionmentioning
confidence: 99%
“…MED152 and Dokdonia sp. MED134 have been published (Gó nzalez et al, 2008(Gó nzalez et al, , 2011. The genome of MED152 has been closed (González et al, unpublished results).…”
Section: Genome Sequencing and Assemblymentioning
confidence: 99%
“…In Polaribacter sp. MED152, it was proposed that PR, in combination with a large suite of light sensing genes and a remarkable number of proteins involved in anaplerotic carbon fixation, represented adaptations to survive in the surface ocean while traveling between particles (Gó nzalez et al, 2008). This bacterium has a relatively small genome and it was postulated that it was only able to use a small number of monomeric carbon compounds, a fact consistent with the very low number of transporters compared with other bacteria and with a lower number of sugars used compared with MED217 (O Nedashkovskaya, personal communication).…”
Section: Genomics Of Marine Bacteroidetes B Fernández-gómez Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…However, exploratory studies such as ours can only provide insight into sequence diversity, generating fundamental questions regarding rhodopsin function and its impact at both cellular and ecosystem levels. A recent analysis by Gonzalez et al (2008) of the genome sequence of a proteorhodopsin-encoding marine bacterium proposed this organism may be capable of both carbon fixation and rhodopsin-based phototrophy. Such ideas highlight the vast potential for novel metabolic strategies involving rhodopsins.…”
Section: Isolate Mwh-uga1 Encodes An Lg1-actrmentioning
confidence: 99%